Parallel Processing Edge Detection Methods for MR Imagery Volumes using CUDA Enabled GPU Machine - Saha, T; Sunitha, R (International Journal of Computer Sciences and Engineering, 2025)
An IoT network is rendered reliable when it is tolerant to faults. Fault management involves fault prevention, detection and recovery of which prevention is considered to be a significant phase. The main objective of this work is fault prevention and detection in IoT networks. The existing IoT fault prevention system finds only one reliable path identified using the goodness value of different available paths and no alternate solutions are provided in case of failure of the reliable path. The proposed system provides a solution by choosing the non-discarded path with the highest goodness value for transmission in case the chosen path fails. The proposed framework has a set of observer nodes connected to a smart gateway and a set of sensor nodes connected to the observers. The gateway acts as the interface between the network and the Internet. This framework comprises prevention and detection algorithms to prevent communication failures between sensor node and gateway, to provide alternative reliable paths for transmission and to detect node faults in early stages. The proposed gateway also provides a solution for hardware failure, software failure, connection failure and also manages the overall load balance of the network.